Niezauważona i rewolucyjna neurohistoria sztuki - Kędziora, Łukasz (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2014)
The article „Omitted and revolutionary Neruoarthistory” is a critical review of John Onians’s book „Neuroarthistory: From Aristotle and Pliny to Baxandall and Zeki”. The main goal of this review is to recount theoretical base of new perspective – neuroarthistory and its practical consequences. Author writes about the mechanism of neuroarthistory and shows two case studies form Onians: Aloisy Riegel and Jasper Johns. Furthermore the article has many critical remarks, regarding new approach and tendency to cognitivisation of humanistic science. On this bases the author tries to answer such q uestions as: how can we connect art. history (science discipline) and neuroscience, how important is developing transdysciplinary research in interpretation of art and why polish scientist do not try to explore neuroarthistory even on its basic level. This article is a fist attempt to introducing neuroarthistory in polish language.